The Effect of Calcination Temperature on Cobalt Oxide Species and Performance for Catalytic Ozonation of NH4+ in Water - Lina Mahardiani (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2019)
Cobalt oxide catalysts can be prepared by impregnation and calcined under different temperature to obtained different species of cobalt oxide, namely CoO(OH), Co3O4, and CoO. Co3O4 was the most appropriate catalyst for decomposing NH4+ with O3 in the presence of Cl– because of relatively high activity, 74%, and high selectivity for gas products, 88%, compared to CoO and CoO(OH). Cl– is necessary to proceed the catalytic ozonation of NH4+ since Cl– participate in the catalytic ozonation mechanism, while SO42– inhibited the process. During the catalytic ozonation of NH4+, Co3O4 showed no deactivation rather than enhanced the catalytic performance after repeated used up to 100% of NH4+ conversion. The Co3O4 can be regenerated by recalcining the catalyst under air at high temperature.